Dust impacts on Mongolian cyclone and cold front in East Asia: a case study during 18–22 March 2010 - Li, Jing; Chen, Shu-Hua (Frontiers in Environmental Science, 2023)
The Gobi Desert in East Asia experiences dust outbreaks during the spring, which are often caused by high winds associated with Mongolian cyclones. The radiative forcing that arises from dust aerosols could affect the intensity and movement of Mongolian cyclones and cold fronts. A case study on a Mongolian cyclone that occurred during 18-22 March 2010 in East Asia examines these factors using an atmosphere-dust coupled model. Our numerical results show that dust’s impact on the intensity of the cyclone and its cold front varies between day and night and depends on the relative position of the weather systems of interest to the dust plume, i.e., the edge or the main dust plume region. When the dust plume approaches the cold front, most of the dust is trapped behind the cold front at low levels, but a small amount of dust extends to the middle levels, thereby reaching the warm side of the middle-level front. As a result, dust weakens the intensity of the low-level front and intensifies the middle-level front during the daytime, modifying the cold front oppositely at night. Dust influences the cyclone in two phases. During the first phase, the dust plume edge arrives at the center of the cyclone in the daytime and warms the region, slightly intensifying the cyclone. During the second phase, the major dust plume feeds into the cyclone center in the early morning. The net dust effect is negative, which cools the cyclone center and decreases or stops the intensification. Subsequently, the cyclone is taken over by a nearby cyclonic circulation downstream. The dust plume approaches the new cyclone center, which repeats a similar pattern of intensity change: intensifying and then leveling off. Our results show that dust has no clear influence on the movement of the cyclone and its cold front.